Teacher’s Roles in Creating an-Active Learning Environment in The Queen’s Classroom Series - Feni Agustin; Adi Yusuf; Nailul Fauziyah (UICELL, 2022)
The role of a teacher is very important because it is very influential in the development of students’ learning. Furthermore, teacher’s roles are very important because they can help teachers know students' understanding, help improve learning, and motivate students during learning process. The purposes of this study were to identify the types of teacher’s roles, to describe how the types are applied by the teacher, and to describe an active learning environment as the effect of the applied roles in The Queen’s Classroom series. This study used a qualitative descriptive method. The data were collected through observation sheets in the form of classifications of teacher’s roles in creating an-active learning environment in The Queen’s Classroom series. The results indicated that 3 types of teacher’s roles were found: teacher as controller, teacher as organizer, and teacher as assessor. Teacher as controller can be seen when Mrs. Ma created a group for this study material at the previous meeting. Mrs. Ma asked students to discuss it with their friends in a group. Teacher as organizer occurred when Mrs. Ma made the rule of class leader so that students scrambled to get excellent and satisfying grades. Teacher as assessor was exemplified when the teacher gave students better scores so that they were motivated to learn more actively. In learning process teacher can guide the students to express and think. Teacher roles can help students to active discussion and make interaction among others. The effect of teacher’s roles make active learning environment. Keywords: Teacher Roles, Active Learning, The Queen’s Classroom series